Recent Experiences in Managing Capital Inflows-Cross-Cutting Themes and Possible Policy Framework. (Policy Papers; Policy Paper, 2011)
Emerging markets (EMs) are experiencing a surge in capital inflows, lifting asset prices and growth prospects. While inflows are typically beneficial for receiving countries, inflow surges can carry macroeconomic and financial stability risks. This paper reviews the recent experience of EMs in dealing with capital inflows and suggests a possible framework for IMF policy advice on the spectrum of measures available to policymakers to manage inflows, including macroeconomic policies, prudential measures and capital controls. Illustrative applications of this framework suggest that it may be appropriate for several countries, based on their current circumstances, to consider prudential measures or capital controls in response to capital inflows. The suggested framework is intended to inform staff policy advice to all Fund members with open capital accounts. It forms part of a broader effort to sharpen Fund surveillance, preserve evenhandedness, and foster greater global policy coordination. As indicated in the Supplement to this paper, this broader effort includes the development of 'global rules of the game' on macroprudential policies, capital account liberalization, and reserve adequacy, and the preparation of spillover reports assessing spillovers from the five systemic economies-all of which will inform the current and broader framework being developed.